The Role of Long-Chain Fatty Acids in Inflammatory Bowel Disease - Ma, Chunxiang; Vasu, Reshma; Zhang, Hu (Mediators of Inflammation, 2019)
Inflammatory bowel disease (IBD) is a complicated disease involving multiple pathogenic factors. The complex relationships between long-chain fatty acids (LCFAs) and the morbidity of IBD drive numerous studies to unravel the underlying mechanisms. A better understanding of the role of LCFAs in IBD will substitute or boost the current IBD therapies, thereby obtaining mucosal healing. In this review, we focused on the roles of LCFAs on the important links of inflammatory regulation in IBD, including in the pathogen recognition phase and in the inflammatory resolving phase, and the effects of LCFAs on immune cells in IBD.